Pore structure control of anodized alumina film and sorption properties of water vapor on CaCl2-aluminum composites. (1st October 2020) - Chumnanwat, Suppanat; Watanabe, Yuto; Taniguchi, Naoko; Higashi, Hidenori; Kodama, Akio; Seto, Takafumi; Otani, Yoshio; Kumita, Mikio
Abstract: Recently, increasing research attention has been given to the development of an absorber to enhance the coefficient of performance (COP) and the capacity of an adsorption heat pump by improving the sorbent in the sorption chamber or reactor. This study introduces the preparation method for an efficient adsorbent with a high thermal conductivity. Three types of host matrix aluminum composite sorbents were prepared through anodizing and pore widening treatment (PWT). This created an aluminum oxide film that was 92 μm thick with a mean pore diameter of 76 nm on an aluminum plate. To improve the sorption ability, the anodized aluminum was impregnated with calcium chloride. The sorption isotherm of the aluminum composite demonstrated its ability to uptake 7.5 mol-H2 O/mol-CaCl2 water at a relative pressure of 0.33 at 30 °C. A numerical method was used to predict water sorption and temperature distribution in the aluminum composite layer via a heat and mass transfer model. The specific cooling power (SCP) was used to indicate the cooling performance of a sorption heat pump that employed the aluminum composite as laminate sorbent fins by varying the spacing between each fin. Highlights: Host matrix structure and deposited CaCl2 affected water sorption abilities. Water uptake and temperature distribution were predicted numerically. The specific cooling performances of sorption cooling system were evaluated.